An online neural substrate for sense of agency. - Chambon, V; Wenke, D; Fleming, S; Prinz, W; Haggard, P (2013)
"Sense of agency" refers to the feeling of controlling an external event through one's own action. On one influential view, sense of agency is inferred after an action, by "retrospectively" comparing actual effects of actions against their intended effects. In contrast, a "prospective" component of agency, generated during action selection, and in advance of knowing the actual effect, has received less attention. Here, we used functional magnetic resonance imaging to investigate prospective contributions of action selection processes to sense of agency. To do so, we dissociated action selection processes from action-outcome matching, by subliminally priming responses to a target. We found that participants experienced greater control over action effects when the action was compatibly versus incompatibly primed. Thus, compatible primes facilitated action selection processing, in turn boosting sense of agency over a subsequent effect. This prospective contribution of action selection processes to sense of agency was accounted for by exchange of signals across a prefrontal-parietal network. Specifically, we found that the angular gyrus (AG) monitors signals relating to action selection in dorsolateral prefrontal cortex, to prospectively inform subjective judgments of control over action outcomes. Online monitoring of these signals by AG might provide the subject with a subjective marker of volition, prior to action itself.